2(x-1)+6x=4(3-1)+2

Simple and best practice solution for 2(x-1)+6x=4(3-1)+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x-1)+6x=4(3-1)+2 equation:


Simplifying
2(x + -1) + 6x = 4(3 + -1) + 2

Reorder the terms:
2(-1 + x) + 6x = 4(3 + -1) + 2
(-1 * 2 + x * 2) + 6x = 4(3 + -1) + 2
(-2 + 2x) + 6x = 4(3 + -1) + 2

Combine like terms: 2x + 6x = 8x
-2 + 8x = 4(3 + -1) + 2

Combine like terms: 3 + -1 = 2
-2 + 8x = 4(2) + 2

Multiply 4 * 2
-2 + 8x = 8 + 2

Combine like terms: 8 + 2 = 10
-2 + 8x = 10

Solving
-2 + 8x = 10

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2' to each side of the equation.
-2 + 2 + 8x = 10 + 2

Combine like terms: -2 + 2 = 0
0 + 8x = 10 + 2
8x = 10 + 2

Combine like terms: 10 + 2 = 12
8x = 12

Divide each side by '8'.
x = 1.5

Simplifying
x = 1.5

See similar equations:

| 8k^2+32-40=0 | | 4y-y=2 | | .6=4/x | | 988=19(k-936) | | 576/x=x | | 40-7x=-8(x-5)-7 | | (5)2/3 | | 9(u+2)=32 | | (5a-2)/3=9 | | 2y-13=-1 | | 12a-6a=30-10a | | x/6=2/4 | | 15*28/3 | | 4b^2+12b-160=0 | | 12x+25x=188-10x | | -14c+11c-12c+11c=20 | | 4m-3m=14 | | .5=x-(.2sin(x)) | | 19=2+8(r-5) | | a^2-4b^2-4b-1=0 | | 8+4xn=-12 | | -3/5x-1/3=-4/5x-1/5 | | 17x+12=124+3x | | 12w-7w-3w=18 | | 14j=-6+13j | | 4n+22= | | 2x+4x-6=5+7 | | 12w-7w-3w=13 | | (8u-12)= | | )-^)/((6z)/(z^2-16)( | | -99=9y | | 14w-6w-8w+2w=14 |

Equations solver categories